Chatbot AI Sebagai Mediator Perceraian Di Indonesia Dalam Tinjauan Hukum Positif - Nur Asvia, Salwa; Miftahur Rohmah, Siti; Nabilah, Zahidah (Interdisciplinary Explorations in Research Journal, 2024)
Abstract Divorce in Indonesia is a complex social problem. Mediation is a more peaceful and constructive alternative to trial. The development of AI technology opens up new opportunities in mediation, including through the use of AI chatbots. This journal analyzes the potential and challenges of using AI chatbots as mediators in divorce cases in Indonesia within the framework of positive law. This research uses a normative juridical research method with a qualitative approach. Data was collected through literature study and legal analysis of relevant laws and regulations. The results showed that AI chatbots have the potential to help improve the accessibility and effectiveness of divorce mediation. AI chatbots can provide legal information and guidance on the mediation process, help disputing parties to identify and understand their issues, and facilitate communication and negotiation between the two parties. However, the use of AI chatbots in divorce mediation also presents some legal challenges. Among them are the limitations of AI in understanding the complexity of human emotions and situations, concerns about the privacy and security of disputants' data, the potential for bias and discrimination in AI algorithms, and the lack of specific legal regulations to govern the use of AI in mediation. The journal recommends several measures to address such legal challenges, such as the development of more sophisticated AI chatbots that are sensitive to the emotional and social context of mediation, the establishment of strict privacy and data security standards, testing and auditing of AI algorithms to ensure fairness and non-discrimination, and the establishment of specific legal regulations to govern the use of AI in mediation. In conclusion, AI chatbots have the potential to be a useful tool in divorce mediation in Indonesia. However, serious efforts need to be made to address the legal challenges associated with its use. Keywords: AI Chatbot, Mediation, Positive Law, Indonesia Abstrak Perceraian di Indonesia merupakan sebuah problematika sosial yang kompleks. Mediasi menjadi alternatif penyelesaian yang lebih damai dan konstruktif dibandingkan dengan persidangan. Perkembangan teknologi AI membuka peluang baru dalam mediasi, termasuk melalui penggunaan chatbot AI. Jurnal ini menganalisis potensi dan tantangan penggunaan chatbot AI sebagai mediator dalam kasus perceraian di Indonesia dalam kerangka hukum positif. Penelitian ini menggunakan metode penelitian yuridis normatif dengan pendekatan kualitatif. Data dikumpulkan melalui studi literatur dan analisis hukum terhadap peraturan perundang-undangan yang relevan. Hasil penelitian menunjukkan bahwa chatbot AI berpotensi untuk membantu meningkatkan aksesibilitas dan efektivitas mediasi perceraian. Chatbot AI dapat memberikan informasi hukum dan panduan proses mediasi, membantu pihak-pihak yang bersengketa untuk mengidentifikasi dan memahami masalah mereka, serta memfasilitasi komunikasi dan negosiasi antara kedua belah pihak. Namun, penggunaan chatbot AI dalam mediasi perceraian juga menghadirkan beberapa tantangan hukum. Diantaranya adalah keterbatasan AI dalam memahami kompleksitas emosi dan situasi manusia, kekhawatiran tentang privasi dan keamanan data pihak-pihak yang bersengketa, potensi bias dan diskriminasi dalam algoritma AI, dan kekurangan regulasi hukum yang spesifik untuk mengatur penggunaan AI dalam mediasi. Jurnal ini merekomendasikan beberapa langkah untuk mengatasi tantangan hukum tersebut, seperti pengembangan chatbot AI yang lebih canggih dan sensitif terhadap konteks emosional dan sosial mediasi, penetapan standar privasi dan keamanan data yang ketat, pengujian dan audit algoritma AI untuk memastikan keadilan dan non-diskriminasi, dan pembentukan regulasi hukum yang spesifik untuk mengatur penggunaan AI dalam mediasi. Kesimpulannya, chatbot AI memiliki potensi untuk menjadi alat yang bermanfaat dalam mediasi perceraian di Indonesia. Namun, perlu dilakukan upaya yang serius untuk mengatasi tantangan hukum yang terkait dengan penggunaannya. Kata Kunci: Chatbot AI, Mediasi, Hukum Positif, Indonesia